Four-year survival with nivolumab in patients with previously treated advanced non-small-cell lung cancer: a pooled analysis. Issue 10 (October 2019) - Antonia, Scott J; Borghaei, Hossein; Ramalingam, Suresh S; Horn, Leora; De Castro Carpeño, Javier; Pluzanski, Adam; Burgio, Marco A; Garassino, Marina; Chow, Laura Q M; Gettinger, Scott; Crinò, Lucio; Planchard, David; et al.
Summary: Background: Phase 3 clinical data has shown higher proportions of patients with objective response, longer response duration, and longer overall survival with nivolumab versus docetaxel in patients with previously treated advanced non-small-cell lung cancer (NSCLC). We aimed to evaluate the long-term benefit of nivolumab and the effect of response and disease control on subsequent survival. Methods: We pooled data from four clinical studies of nivolumab in patients with previously treated NSCLC (CheckMate 017, 057, 063, and 003) to evaluate survival outcomes. Trials of nivolumab in the second-line or later setting with at least 4 years follow-up were included. Comparisons of nivolumab versus docetaxel included all randomised patients from the phase 3 CheckMate 017 and 057 studies. We did landmark analyses by response status at 6 months to determine post-landmark survival outcomes. We excluded patients who did not have a radiographic tumour assessment at 6 months. Safety analyses included all patients who received at least one dose of nivolumab. Findings: Across all four studies, 4-year overall survival with nivolumab was 14% (95% CI 11–17) for all patients (n=664), 19% (15–24) for those with at least 1% PD-L1 expression, and 11% (7–16) for those with less than 1% PD-L1 expression. In CheckMate 017 and 057, 4-year overall survival was 14% (95% CI 11–18) in patients treated with nivolumab, compared with 5% (3–7) in patients treated with docetaxel. Survival subsequent to response at 6 months on nivolumab or docetaxel was longer than after progressive disease at 6 months, with hazard ratios for overall survival of 0·18 (95% 0·12–0·27) for nivolumab and 0·43 (0·29–0·65) for docetaxel; for stable disease versus progressive disease, hazard ratios were 0·52 (0·37–0·71) for nivolumab and 0·80 (0·61–1·04) for docetaxel. Long-term data did not show any new safety signals. Interpretation: Patients with advanced NSCLC treated with nivolumab achieved a greater duration of response compared with patients treated with docetaxel, which was associated with a long-term survival advantage. Funding: Bristol-Myers Squibb.